Absence of in vivo mutagenicity of multi-walled carbon nanotubes in single intratracheal instillation study using F344 gpt delta rats. (December 2017) - Horibata, Katsuyoshi; Ukai, Akiko; Ogata, Akio; Nakae, Dai; Ando, Hiroshi; Kubo, Yoshikazu; Nagasawa, Akemichi; Yuzawa, Katsuhiro; Honma, Masamitsu
Abstract Introduction It is known that fibrous particles of micrometer length, such as carbon nanotubes, which have same dimensions as asbestos, are carcinogenic. Carcinogenicity of nanomaterials is strongly related to inflammatory reactions; however, the genotoxicity mechanism(s) is unclear. Indeed, inconsistent results on genotoxicity of multi-walled carbon nanotubes (MWCNTs) have been shown in several reports. Therefore, we analyzed the in vivo genotoxicity induced by an intratracheal instillation of straight MWCNTs in rats using a different test system—thePig-a gene mutation assay—that can reflect the genotoxicity occurring in the bone marrow. Since lungs were directly exposed to MWCNTs upon intratracheal instillation, we also performed thegpt assay using the lungs. Findings We detected no significant differences inPig-a mutant frequencies (MFs) between the MWCNT-treated and control rats. Additionally, we detected no significant differences ingpt MFs in the lung between the MWCNT-treated and control rats. Conclusions Our findings indicated that a single intratracheal instillation of MWCNTs was non-mutagenic to both the bone marrow and lung of rats.